Experience with the safe admission of breast and thyroid cancer patients in non-endemic areas during an epidemic outbreak - Tang, Peng; Ai, Xiang; Wang, Minghao; Hu, Ying; Pan, Qinwen; Jiang, Jun (Frontiers in Oncology, 2023)
Background The outbreaks of infectious diseases, such as coronavirus disease 2019 (COVID-19), have seriously affected the normal work and life of the public, as well as the normal diagnosis and treatment of other diseases due to their strong infectivity, high population susceptibility, and diverse clinical manifestations. Breast and thyroid specialists in non-hotspot epidemic areas of COVID-19 must consider factors, including epidemic prevention and control, breast and thyroid cancers and diseases diagnosis and treatment, and access to medical resources to make a reasonable treatment choice and optimize the treatment process. Methods A cohort study was designed under our center’s epidemic prevention and control strategy. The study was conducted between February 3 and April 19, 2020, to explore the safety of clinical diagnosis and treatment of breast and thyroid cancer patients during the epidemic. All the outpatients, inpatients, day-time chemotherapy patients, targeted therapy patients, and relevant medical staff in the observation period in the Department of Breast and Thyroid Surgery in Southwest Hospital in Chongqing municipality, China, were included to investigate the detection and infection rate of COVID-19 and suspected patients. Results During the observation period, 27,117 patients were admitted to the outpatient unit. We performed 394 inpatient surgeries and 411 day-time surgeries. In our center, 1,046 and 663 patients received day-time chemotherapy and targeted therapy, respectively. All the patients were diagnosed and treated promptly and safely. Three suspected COVID-19 patients were identified in the outpatient unit. Healthcare staff achieved a “zero” infection of COVID-19. Conclusion The spread and cross-infection of COVID-19 can be avoided in non-hotspot epidemic areas based on scientific prevention and control, and cancer patients can be diagnosed and treated on time. The prevention and control measure implemented in the COVID-19 epidemic for diagnosing and treating cancer patients was effective and can be referenced for other infectious disease outbreaks.